Value Co-Creation: A Strategy for Enhancing Inclusiveness in Special Education - Pennee Narot; Narong Kiettikunwong (MDPI AG, 2024)
This qualitative study examines the educational management practices of a municipality in Thailand by evaluating the current delivery of special educational services with underlying principles rooted in value co-creation (VCC)-a business concept often employed to enhance engagement and participation with the aim of creating mutual value. The study's objective is to identify gaps in real-life practices. The research methodology encompasses in-depth interviews with key stakeholders, focus group discussions involving school board members and parents, and content analysis to extract core concepts for policy recommendations. The study's findings reveal that the municipality is increasingly recognizing the potential of VCC in enhancing student outcomes, particularly for those with special educational needs. However, challenges stemming from schools' financial constraints and the influx of students from lower socio-economic backgrounds impede the full realization of VCC principles. Consequently, it is crucial for the government to prioritize the alignment of VCC strategies with special education. This can be achieved by considering reengineering the education budget allocation and making investments, whether direct or indirect, to support the VCC process. These measures are essential to promote the evolution of VCC and sustain special educational service operations effectively.